2018
DOI: 10.1038/s41598-018-29585-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance based sensor for the detection of glycopeptide antibiotics in milk using rationally designed nanoMIPs

Abstract: Glycopeptide antibiotics are known as the last resort for the treatment of serious infections caused by Gram-positive bacteria. The use of milk products contaminated with these antibiotic residues leads to allergic reactions and sensitivity in human. Also, long-term consumption of milk products containing low levels of these antibiotics may cause the relevant bacteria to build up resistance to these last resort antibiotics. Sensitive, rapid and effective quantification and monitoring systems play a key role fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 34 publications
(52 reference statements)
0
33
0
Order By: Relevance
“…The sensor could differentiate the lowest concentration of DNA (0.002) and negative control ( Figure 8 B) and showed a good reproducibility in a wide investigation range ( Figure 8 C). The LOD was verified based on the linear portion of the saturation graph by calculating three times the standard deviation of the blank response (0.4 × 3 = 1.2 nA) and extrapolating the sensor signal in the linear calibration curve to convert the value to concentration [ 34 ]. The limit of detection was determined to be 0.94 nM with a linear range from 2 to 20 nM, as shown in Figure 8 D.…”
Section: Resultsmentioning
confidence: 99%
“…The sensor could differentiate the lowest concentration of DNA (0.002) and negative control ( Figure 8 B) and showed a good reproducibility in a wide investigation range ( Figure 8 C). The LOD was verified based on the linear portion of the saturation graph by calculating three times the standard deviation of the blank response (0.4 × 3 = 1.2 nA) and extrapolating the sensor signal in the linear calibration curve to convert the value to concentration [ 34 ]. The limit of detection was determined to be 0.94 nM with a linear range from 2 to 20 nM, as shown in Figure 8 D.…”
Section: Resultsmentioning
confidence: 99%
“…SPR can be considered as one of the most powerful, and therefore popular, readout technologies and has been combined with MIPs for the detection of microorganisms [ 174 , 175 ], amino acids, peptides and proteins [ [176] , [177] , [178] ], dangerous explosives [ [179] , [180] , [181] ], antibiotics [ [182] , [183] , [184] ] and other low-molecular weight compounds [ [185] , [186] , [187] , [188] , [189] ]. Detection upon rebinding of the target is based on changes in electron density at the surface of the sensor chip.…”
Section: Mips As Receptors In Sensing Devicesmentioning
confidence: 99%
“…According to our statistical analysis, only a few studies have recently reported on photoelectrochemical (PEC) GQD sensors in comparison to optical and electrochemical sensors. At the same time, various studies have been carried out using SPR sensors for drug monitoring and disease detection [340][341][342][343], but surprisingly only two such studies have reported on the use of GQDs. Given this, despite SPR sensors being optical sensors, we have compiled them in this section.…”
Section: Photoelectrochemical and Miscellaneous Gqd Sensors In Biomedmentioning
confidence: 99%